Does Circadian Rhythm Affect the Pharmacokinetics of Once-Daily Tobramycin in Adults With Cystic Fibrosis?. Issue 4 (August 2020) - van Maarseveen, Erik M.; van der Meer, Renske; Neef, Cees; Heijerman, Harry G. M.; Touw, Daniel J.
Abstract : Background: In the era of multiple daily dosing of systemic aminoglycosides, a circadian rhythm in the clearance of these vital antibiotics has been demonstrated in animals and healthy volunteers. Over the past decade, once-daily dosing regimens have been proved to be less nephrotoxic and were therefore adopted worldwide for most indications requiring treatment with an aminoglycoside. In this study, the effect of the time of administration on the pharmacokinetics of once-daily tobramycin in adults with cystic fibrosis (CF) experiencing a pulmonary exacerbation was investigated. Methods: In this open randomized study, patients with CF received intravenous tobramycin at 8:00 or 22:00 hours. Pharmacokinetic and kidney function parameters were compared between the 2 groups. Results: Twenty-five patients were included. The mean weight-corrected clearances of tobramycin were 1.46 versus 1.43 mL/h*kg ( P = 0.50) and mean volumes of distribution were 0.25 versus 0.27 L/kg ( P = 0.54) for the 8:00 and 22:00 groups, respectively. In addition, no significant differences were detected in changes in estimated clearances of creatinine or tobramycin on day 1 and day 8 in the 8:00 or 22:00 group, indicating that there was no decline in clearance over time. At day 8 of therapy, the increase in serum blood urea nitrogen in the 22:00 group was significantly higher than that in the 8:00 group (1.8 versus 0.2 mmol/L, P = 0.015). Conclusions: The time of administration (8:00 versus 22:00) did not affect tobramycin pharmacokinetics in the adult CF population studied. The increase in serum blood urea nitrogen in the 22:00 group requires further investigation.